EMIL DARDAK'S CAMPAIGN STRATEGY IN WINNING KHOFIFAH-EMIL IN REGIONAL HEAD ELECTIONS EAST JAVA 2018 - Eva, Masriniati; Budianto, Heri (IJOSMAS, 2023)
Political campaigns in a democratic stage are an important tool to gain victory. Therefore, political actors must be able to choose what strategy will be implemented to achieve this goal. In this research, the main focus being studied is Emil Dardak's campaign strategy in winning the 2018 East Java Pilgub with his partner Khofifah . The research focuses on the study of Emil Dardak's strategy. The method used is descriptive qualitative by describing Emil Dardak's political campaign strategy to win the 2018 East Java Pilgub Election. In the research process, Emil was assisted by a qualified winning team. A populist campaign strategy, intense approach, personal touch is Emil's strategy in reaching prospective voters who have previously been determined based on voter segments based on elements of location, beliefs, age and social background. Besides that, determining